246 views
5 votes
-18 - 6n= 6 (1 + 3n)

User Joel Vroom
by
5.0k points

2 Answers

3 votes

Answer:-1

Step-by-step explanation:-18-6n = 6 + 18n

-6n=6

divide

n=-1

User Sharan Mohandas
by
5.6k points
4 votes

Answer:

-1

Explanation:

First, divide by 6

-18/6- 6n/6=6/6(1+3n)

-3-n= 1+3n

Then move the variable to one side

-3-n+n= 1+3n+n

-3=1+4n

Then isolate the variable

-3-1=1-1+4n

-4=4n

Isolate more

-4/4=4n

-1=n

User Hamidreza Nikoonia
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.